A Giant Posterior Mediastinal Metastatic Mass of GIST Gastric Origin - Samender Randhawa; Abeeha Naqvi; Mathew Thomas; Prashanth Ashok Kumar; Rahul Seth (Annals of Internal Medicine: Clinical Cases)
Gastrointestinal stromal tumors (GISTs) are uncommon visceral sarcomas that predominantly arise from the gastrointestinal tract, particularly from interstitial cells of Cajal. Although the liver is a common site for metastasis, rarely GISTs show extraintestinal manifestation in the bone and lungs. We report a case patient with an uncommon location and unusually large GIST metastasis as a mediastinal mass 3 years after undergoing total gastrectomy and chemotherapy with imatinib, a tyrosine kinase inhibitor.